Competitive Interactions Between Incompatible Mutants of the Social Bacterium Myxococcus xanthus DK1622 - Gong, Ya; Zhang, Zheng; Zhou, Xiu-wen; Anwar, Mian N.; Hu, Xiao-zhuang; Li, Ze-shuo; Chen, Xiao-jing; Li, Yue-zhong (Frontiers in Microbiology, 2018)
Due to the high similarity in their requirements for space and food, close bacterial relatives may be each other’s strongest competitors. Close bacterial relatives often form visible boundaries to separate their swarming colonies, a phenomenon termed colony-merger incompatibility. While bacterial species are known to have many incompatible strains, it is largely unclear which traits lead to multiple incompatibilities and the interactions between multiple incompatible siblings. To investigate the competitive interactions of closely related incompatible strains, we mutated Myxococcus xanthus DK1622, a predatory bacterium with complex social behavior. From 3392 random transposon mutations, we obtained 11 self-identification (SI) deficient mutants that formed unmerged colony boundaries with the ancestral strain. The mutations were at nine loci with unknown functions and formed nine independent SI mutants. Compared with their ancestral strain, most of the SI mutants showed reduced growth, swarming and development abilities, but some remained unchanged from their monocultures. When pairwise mixed with their ancestral strain for co-cultivation, these mutants exhibited improved, reduced or unchanged competitive abilities compared with the ancestral strain. The sporulation efficiencies were affected by the DK1622 partner, ranging from almost complete inhibition to 360% stimulation. The differences in competitive growth between the SI mutants and DK1622 were highly correlated with the differences in their sporulation efficiencies. However, the competitive efficiencies of the mutants in mixture were inconsistent with their growth or sporulation abilities in monocultures. We propose that the colony-merger incompatibility in M. xanthus is associated with multiple independent genetic loci, and the incompatible strains hold competitive interaction abilities, which probably determine the complex relationships between multiple incompatible M. xanthus strains and their co-existence strategies.